Significant enhancement of the bias stability of Zn-O-N thin-film transistors via Si doping - Song, Aeran (Sci Rep, 2020)
Si doping was used to significantly improve the bias stability of ZnON thin-film transistors. Si 3 W (~1%) doped ZnON TFTs showed a saturation mobility of 19.70 cm(2)/Vs along with remarkable improvements in the threshold voltage shift for negative gate bias stress (NBS) within 1.69 V. The effects of Si doping were interpreted by the experimental correlation between device performance and physical analysis, as well as by the theoretical calculation. Si doping induces the reduction of N-related defects by increasing stoichiometric Zn(3)N(2), and decreasing nonstoichiometric Zn(x)N(y). In addition, Si doping reduces the band edge states below the conduction band. According to density functional theory (DFT) calculations, Si, when it substitutes for Zn, acts as a carrier suppressor in the ZnON matrix.